Evaluation of Change Management Innovation Training Based on Participant Perception - Sembiring, Helena; Mahendra Wirawan, Sri; Indrastuti (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2024)
This research was conducted to find out how effective Management of Change and Innovation, CMI training is in increasing participants' understanding of the CMI concept. Organizational change is triggered by changes such as dynamic regulations, societal demands for better public services, and technological advances. Public organizations must change, make continuous improvements, and move towards High Performance Public Organizations to achieve their best performance. In the three groups of participants in this study, there was an average increase of 52,23% from pre-test to post-test. Cohort IV showed the greatest improvement, while participant satisfaction levels varied, with Cohort V showing higher levels of satisfaction than Cohorts IV and VI. According to the evaluation of the implementation of innovation proposals, more than 65,47% of participants successfully implemented innovative proposals in their workplace. This shows that participants are very interested in innovation. The evaluation results stated that the CMI training was successful in increasing participants' understanding, but variations in participant satisfaction needed further attention. Evaluation and in-depth study of participant feedback is the key to improving the quality of CMI training services. A further training evaluation of the variables that influence the level of participants' understanding and the effectiveness of the training is needed, as well as the importance of planning improvements based on the evaluation results so that the training program can continue to develop and provide maximum benefits for participants in the future.